Micro RNA‐induced gene silencing strategy for the delivery of siRNAs targeting Meloidogyne incognita in a model plant Nicotiana benthamiana. Issue 7 (13th April 2021) - Hada, Alkesh; Patil, Basavaprabhu L; Bajpai, Akansha; Kesiraju, Karthik; Dinesh‐Kumar, Savithramma; Paraselli, Bheema; Sreevathsa, Rohini; Rao, Uma
Abstract: BACKGROUND: Occurrence of multiple biotic stresses on crop plants result in drastic yield losses which may have severe impact on the food security. It is a challenge to design strategies for simultaneous management of these multiple stresses. Hence, establishment of innovative approaches that aid in their management is critical. Here, we have introgressed a micro RNA‐induced gene silencing (MIGS) based combinatorial gene construct containing seven target gene sequences of cotton leaf curl disease (CLCuD), cotton leaf hopper ( Amrasca biguttula biguttula ), cotton whitefly ( Bemisia tabaci ) and root‐knot nematode ( Meloidogyne incognita ). RESULTS: Stable transgenic lines of Nicotiana benthamiana were generated with the T‐DNA harboring Arabidopsis miR173 target site fused to fragments of Sec23 and ecdysone receptor ( EcR ) genes of cotton leaf hopper and cotton whitefly. It also contained C2/replication associated protein (C2/Rep) and C4 (movement protein) along with βC1 gene of betasatellite to target CLCuD, and two FMRFamide‐like peptide (FLP) genes, Mi‐flp14 and Mi‐flp18 of M. incognita . These transgenic plants were assessed for the amenability of MIGS approach for pest control by efficacy evaluation against M. incognita . Results showed successful production of small interfering RNA (siRNA) through the tasiRNA (trans‐acting siRNA) pathway in the transgenic plants corresponding to Mi‐flp18 gene. Furthermore, we observed reduced Mi‐flp14 and Mi‐flp18 transcripts (up to 2.37 ± 0.12‐fold) in females extracted from transgenic plants. The average number of galls, total endoparasites, egg masses and number of eggs per egg mass reduced were in the range 27–62%, 39–70%, 38–65% and 34–49%, respectively. More importantly, MIGS transgenic plants showed 80% reduction in the nematode multiplication factor (MF). CONCLUSION: This study demonstrates successful validation of the MIGS approach in the model plant, N. benthamiana for efficacy against M. incognita, as a prelude to translation to cotton. © 2021 Society of Chemical Industry. Abstract : We demonstrated successful validation of the miRNA‐induced gene silencing approach in the Nicotiana benthamiana for efficacy against root‐knot nematode. The generated transgenic plants showed 80% reduction in the nematode multiplication factor. © 2021 Society of Chemical Industry.